2012
DOI: 10.1111/j.1365-2435.2012.02038.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect interactions in seagrasses: fish herbivores increase predation risk to sea urchins by modifying plant traits

Abstract: Summary 1.The dominant paradigm of top-down control of ecological communities through direct consumption pathways is giving way to a more nuanced understanding of trophic interactions with the recognition that subtler indirect effects can often play an important role in structuring communities. Direct and indirect trophic and non-trophic processes could well be acting simultaneously within the same food web, and their overall effects may even interact with each other. 2. We studied indirect interactions in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 64 publications
5
45
1
Order By: Relevance
“…Such a view is consistent with the fact that, in Shark Bay, over 800 km further north, P. octolineatus was the dominant grazer of seagrasses in the extensive meadows of a sub-tropical embayment, where this omnivore consumes whole blades and is considered likely to play a significant role in removing leaf tissue from the abundant seagrass species Halophila spinulosa (Burkholder et al 2012). This parallels the high levels of herbivory by Sarpa salpa in the Mediterranean Sea (Pagès et al 2012) and Leptoscarus vaigiensis in IndoPacific waters (Unsworth et al 2007), and the strong influence of these dominant grazers on the structure and function of their associated seagrass ecosystems. One of the most striking features of P. octolineatus on the lower western Australian coast is its marked seasonal pattern of growth, presumably reflecting the limited period in which water temperatures are conducive to growth.…”
Section: Reproductive Biologysupporting
confidence: 66%
“…Such a view is consistent with the fact that, in Shark Bay, over 800 km further north, P. octolineatus was the dominant grazer of seagrasses in the extensive meadows of a sub-tropical embayment, where this omnivore consumes whole blades and is considered likely to play a significant role in removing leaf tissue from the abundant seagrass species Halophila spinulosa (Burkholder et al 2012). This parallels the high levels of herbivory by Sarpa salpa in the Mediterranean Sea (Pagès et al 2012) and Leptoscarus vaigiensis in IndoPacific waters (Unsworth et al 2007), and the strong influence of these dominant grazers on the structure and function of their associated seagrass ecosystems. One of the most striking features of P. octolineatus on the lower western Australian coast is its marked seasonal pattern of growth, presumably reflecting the limited period in which water temperatures are conducive to growth.…”
Section: Reproductive Biologysupporting
confidence: 66%
“…Fish productivity was found to be lower in seagrass meadows grazed by green turtles (Arthur et al, 2013) and after meadow collapse caused by overgrazing (reported for turtles in (Christianen et al, 2013). Similarly, herbivorous fishes, dugongs, geese and other waterbirds have been found to drastically reduce invertebrate biomass in seagrass meadows and salt marshes (Marklund et al, 2002;Sherfy and Kirkpatrick, 2003;Skilleter et al, 2007;Pages et al, 2012) . Impacts on invertebrates may occur even where the proportional reduction of vegetation is low (Bortolus et al, 1998).…”
Section: Habitat For Other Organismsmentioning
confidence: 99%
“…However, relatively little of this biomass is directly consumed by grazers, owing to various deterrent compounds [38,39]. Only a few herbivores, sometimes reaching high densities, are able to consume the abundant green leaf biomass, most notably sea urchins [40], some isopods [41] and a few fishes [42]. As predicted, modelled food availability does not necessarily correspond to food consumption.…”
Section: Discussionmentioning
confidence: 99%